Annotated checklist for the Gorgonocephalidae family (Echinodermata: Ophiuroidea) from the National Echinoderm Collection “Dra. Ma. E. Caso M.” of the Instituto de Ciencias del Mar y Limnología, UNAM - Ramírez-Moreno, Frida-Jacqueline (2021)
Introduction: The order Euryalida is represented by fragile ophiuroids with long and slender arms that can be ramified. Species within the family Gorgonocephalidae are characterized by the presence of tiny hooklets on the dorsal aspect of their arms. There are very few published studies referring to species of the family Gorgonocephalidae inhabiting Mexican waters. Objective: To review the taxonomic status of the species belonging to this taxonomic family, identifying their diagnostic taxonomic characteristics to create an illustrated guide of species kept at the CNE, UNAM. Methods: Specialized bibliography of the Gorgonocephalidae family was gathered. Subsequently, all the specimens from the CNE were photographed using Scanning Electron and Multifocal Microscopy photography, to show the structures of taxonomic relevance. Results: A total of 193 specimens corresponding to eight genera and nine species were reviewed. The genus Astrocaneum presented the highest species richness. Conclusions: For the species identified in this study and for the sake of accurate identification, morphological characters such as the shape of hooklets and arm plates were highlighted.